Prolonged cardiac arrest complicating a massive ST-segment elevation myocardial infarction associated with marijuana consumption - Jose Orsini; Christa Blaak; Salil Rajayer; Vikash Gurung; Eric Tam; Joaquin Morante; Ben Shamian; Ryan Malik (Greater Baltimore Medical Center, 2016)
Recreational substance use and misuse constitute a major public health issue. The annual rate of recreational drug overdose-related deaths is increasing exponentially, making unintentional overdose as the leading cause of injury-related deaths in the United States. Marijuana is the most widely used recreational illicit drug, with approximately 200 million users worldwide. Although it is generally regarded as having low acute toxicity, heavy marijuana usage has been associated with life-threatening consequences. Marijuana is increasingly becoming legal in the United States for both medical and recreational use. Although the most commonly seen adverse effects resulting from its consumption are typically associated with neurobehavioral and gastrointestinal symptoms, cases of severe toxicity involving the cardiovascular system have been reported. In this report, the authors describe a case of cannabis-associated ST-segment elevation myocardial infarction leading to a prolonged cardiac arrest.